The Effect of Discovery Learning Method on Students’ Self-Motivation Through Online Learning During The Covid-19 Pandemic - Valen Fridolin Simak; Meivi Sesanelvira A. D. Islam; Muhammad Nurmansyah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: The learning process at the university level, especially in nursing, has changed since the number of cases of COVID-19 has continued to increase. Various problems after one year of the pandemic include students complained of boredom and lack of focus on learning compared to conventional learning in the classroom. The aim of this study was to analyze the effect of discovery learning method on students’ self-motivation through online learning in the COVID-19 pandemic.Method: This study used a quasi-experimental with pre-post control group design and conducted in two areas, PSIK Sam Ratulangi University as an Intervention group and PSIK Stikes Jendral Achmad Yani Cimahi as control group. We recruited a total sample of 82 respondents in total. This study lasted for four weeks with six stages described as two t meetings a week. To measure students' self-motivation, the Motivated Strategies for Learning Questionnaire (MSLQ) instrument totaling 32 items was used. Data were analyzed using Wilcoxon test and Mann Whitney test.Results: The results of this study indicate that there is a significant effect of discovery learning methods with self-motivation in online learning in community nursing course [p=0.00; Z = -2.28] and emergency nursing course [p=0.00; Z = -3.43].Conclusions: The results of the study are promising as the course can have a direct effect on the nursing education system, especially in improving the quality of learning methods. This method may be used as a way to improve student skill in the nursing courses especially community nursing and emergency nursing.